Analisis Perbandingan ANALISIS PERBANDINGAN EFEKTIVITAS DAN KONTRIBUSI PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) PADA SELURUH KABUPATEN DI WILAYAH MINAHASA - Suwetja, I Gede; Tirayoh, Victorina Zusana; Latjandu, Lady Diana (FEB Universitas Sam Ratulangi Manado, 2024)
Abstract. Regional Tax is a mandatory contribution to the region that is owed by an individual or entity that is coercive based on the law by not getting direct compensation and is used for regional purposes for the maximum prosperity of the people. Regional Original Revenue (PAD) is the revenue obtained by the region from sources within its own territory which is collected based on regional regulations in accordance with applicable laws and regulations. The Minahasa region is located in North Sulawesi Province which consists of Minahasa Regency, South Minahasa Regency, North Minahasa Regency, and Southeast Minahasa Regency. The purpose of this study is to compare the effectiveness and contribution of regional taxes to PAD in 4 districts in the Minahasa area in 2019-2023. Minahasa Regency and Southeast Minahasa Regency have been effective and even very effective in their regional tax revenues, while South Minahasa Regency is quite effective in 2021 and North Minahasa is still less effective in 2020 and quite effective in 2021. Meanwhile, the level of regional tax contribution to local revenue in North Minahasa Regency is very good compared to Minahasa Regency, South Minahasa Regency, and Southeast Minahasa.